2023
DOI: 10.1038/s41396-023-01356-6
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial volatile organic compounds attenuate pathogen virulence via evolutionary trade-offs

Abstract: Volatile organic compounds (VOCs) produced by soil bacteria have been shown to exert plant pathogen biocontrol potential owing to their strong antimicrobial activity. While the impact of VOCs on soil microbial ecology is well established, their effect on plant pathogen evolution is yet poorly understood. Here we experimentally investigated how plant-pathogenic Ralstonia solanacearum bacterium adapts to VOC-mixture produced by a biocontrol Bacillus amyloliquefaciens T-5 bacterium and how these adaptations might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…The Bacillus VOCs assay showed that these strains, FZB42, NMTD17, and LLTC93‐VOCs, had higher antifungal activity against R. solani and antibacterial activity of Xoo compared to control. Similarly, certain VOCs against R. solani and R. solanacearum were evaluated using the Bacillus VOCs previously identified through GC–MS (Guo et al, 2023; Wang et al, 2023). The synthetic VOCs, PDC, BDH, 1,2‐BIT, and MIX‐VOCs were explored, indicating strong antimicrobial activity against R. solani and Xoo diseases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Bacillus VOCs assay showed that these strains, FZB42, NMTD17, and LLTC93‐VOCs, had higher antifungal activity against R. solani and antibacterial activity of Xoo compared to control. Similarly, certain VOCs against R. solani and R. solanacearum were evaluated using the Bacillus VOCs previously identified through GC–MS (Guo et al, 2023; Wang et al, 2023). The synthetic VOCs, PDC, BDH, 1,2‐BIT, and MIX‐VOCs were explored, indicating strong antimicrobial activity against R. solani and Xoo diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the VOC mixture was prepared by mixing three individual VOC compounds in the same ratio as they are produced by selected Bacillus spp. after 3 days of growth in the LB (Wang et al, 2023). Different concentrations (5, 10, 20, 40, and 80 μg mL −1 ) of synthetic VOCs were prepared from their respective stock solutions (1 mg mL −1 ) for their antimicrobial potential.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the activity of these volatile compounds extends beyond growth inhibition, as they can modulate Ralstonia metabolism to suppress virulence [108]. Furthermore, it has been observed that R. solanacearum could acquire resistance to the volatiles produced by Bacillus amyloliquefaciens T-5 but will lose the virulence factors responsible for its pathogenicity [109]. This phenomenon can alter the plant pathogen evolution toward decreased virulence.…”
Section: Production Of Volatile Organic Compoundsmentioning
confidence: 99%